Świątynie Wenus Erycyńskiej w starożytnym Rzymie = The temples of Venus Erycina in ancient Rome - Franczak, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the Second Punic War the Romans brought from Sicili cult of a goddess identified withVenera and called her Venus Erycina. The first temple dedicated to her was built in the City centreon the Capitoline Hill in 215 B.C. The second one was built in 181 B.C. this time however,outside the religious boundary of the City, ?extra portam Collinam. Bringing the cult of VenusErycina to Rome was undoubtedly connected with the defeat of the Roman army by the Carthaginianarmy at Trasimene. Consul Gaius Flaminius died at the battle and the Romans lost 15thousand soldiers.
Keywords: Wenus Erycyńska; Rzym - architektura; Rzym - historia; świątynie starożytne; 3 w. p.n.e.